THE FIGHT AGAINST TERRORISM AS ONE OF THE MAIN AREAS OF ACTIVITY FOR THE CUSTOMS AUTHORITIES OF THE NEW UZBEKISTAN: THE LEGAL FRAMEWORK AND INTERNATIONAL COOPERATION (International journal of artificial intelligence, 2026)
This article examines the evolving role of the customs authorities of the Republic of Uzbekistan within the national and regional counter-terrorism framework, in the context of the ‘New Uzbekistan’ development strategy. Based on a comprehensive analysis of domestic legislation, international obligations within the framework of the SCO, the CIS and UN instruments, as well as international documents relating to the World Customs Organisation (WCO). This thesis examines how customs authorities act as the first line of defence against threats to economic security, the movement of materials of a religious-extremist nature across customs borders, and the prevention of terrorist financing. Systemic gaps in current legislation are identified, an original three-tier model of the ‘Customs Anti-Terrorism Shield’ (CATS) is proposed, and specific recommendations are formulated for bringing national customs law into line with international standards.